Safety and Effectiveness of High-Precision Hyperthermic Intraperitoneal Perfusion Chemotherapy in Peritoneal Carcinomatosis: A Real-World Study - Ba, Mingchen; Cui, Shuzhong; Long, Hui; Gong, Yuanfeng; Wu, Yinbing; Lin, Kunpeng; Tu, Yinuo; Zhang, Bohuo; Wu, Wanbo (Frontiers in Oncology, 2021)
Background: Hyperthermic intraperitoneal chemotherapy (HIPEC) has been reported to effectively control peritoneal carcinomatosis (PC) in various patient populations, but there is a lack of real-world data. This study aimed to examine the safety and effectiveness of HIPEC in patients with PC in a real-world setting. Methods: This was a retrospective study of patients with PC treated with the high-precision BR-TRG-I type HIPEC device between 12/2006 and 12/2016. Vital signs during HIPEC and adverse events were recorded. Effectiveness was evaluated by total objective remission rate (ORR), which was based on ascites’ remission 4 weeks after HIPEC. Results: A total of 1200 patients were included. There were 518 males and 682 females, with a mean age of 58.6±6.5 years (range, 32-76 years). Among the patients, 93.6% of the patients (1123/1200) successfully received the three sessions of HIPEC, 158 had massive ascites. The changes of vital signs during HIPEC were within acceptable ranges, and patients only had a transient fever and abdominal distension. Regarding the HIPEC-related complications, hemorrhage was observed in seven (0.6%) patients, anastomotic leakage in four (0.5%), and intestinal obstruction in eight (0.7%). Nine (0.8%, 9/1200) patients had CTCAE grade IV bone marrow suppression, and three (0.3%, 3/1200) patients had severe renal failure (SRF), which were considered to be drug-related. The ORR of malignant ascites was 95.6% (151/158). Conclusion: This real-world study strongly suggests that HIPEC was safe in treating PC patients with a low rate of adverse events and leads to benefits in PC patients with massive malignant ascites.